2023
DOI: 10.3389/fsurg.2022.1047603
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of osteoporosis from proximal femoral cortical bone thickness and Hounsfield unit value with clinical significance

Abstract: BackgroundUtilizing dual-energy x-ray absorptiometry (DXA) to assess bone mineral density (BMD) was not routine in many clinical scenarios, leading to missed diagnoses of osteoporosis. The objective of this study is to obtain effective parameters from hip computer tomography (CT) to screen patients with osteoporosis and predict their clinical outcomes.MethodsA total of 375 patients with hip CT scans for intertrochanteric fracture were included. Among them, 56 patients possessed the data of both hip CT scans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Multiple studies have used the Hu value to determine osteoporosis demonstrated the prediction value of CT in osteoporosis. 29 , 30 , 31 Because CT has higher imaging resolution in identifying bone trabeculae, bone density, and bone cortex, our model is more accurate in predicting the probability of re‐fracture compared to previous studies using X‐rays.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have used the Hu value to determine osteoporosis demonstrated the prediction value of CT in osteoporosis. 29 , 30 , 31 Because CT has higher imaging resolution in identifying bone trabeculae, bone density, and bone cortex, our model is more accurate in predicting the probability of re‐fracture compared to previous studies using X‐rays.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, in-scan calibration prevents a retrospective application. In response to this limitation, alternative indicators for bone density, including HU-based measurements and cortical thickness ratio, have been suggested [8][9][10][11]. However, these methods are subject to various limitations.…”
Section: Introductionmentioning
confidence: 99%